Em Mamrê, a visita da promessa: um estudo de Gênesis 18,1 15 e suas perspectivas teológicas e éticas - Negro, Mauro (2012)
The text of Genesis 18,1 5 is important within the cycle of Abraham. Literary and theological analysis of this sense of perícope demonstrates very patriarchal reports. The goal of this dissertation is to do this analysis, especially demonstrating his "literary movement" or, as it is appropriate to say, his "literary beauty". This research takes the theological and ethi-cal considerations that relates with the other patriarchal traditions of Genesis. It is the study of Genesis 18.1 15 for his literary position in all the patriarchal ac-counts and especially with regard to Abraham. It is in half his life narrated in the text. Until that time, exposed in the text, he just waited for the fulfillment of promises, but nothing actu-ally happened. The end of life approaches with the accumulation of years. When least expec-ted the old promises, behold, the Lord, your God, appears and all is happening. The text is a moment of great expressiveness and narrative raises ethical perspective, using a sign lan-guage. The fundamental hypothesis is the centrality of literary text and its gestural expressi-veness that value the character Abraham, the other cited characters and their actions. The fundamental methodological theoretical aspect was used to read the text careful-ly, synchronous to its movement, always from the grammatical forms and guessing what the fundamental hypothesis suggested its expressiveness. She was always outstanding. The literary analysis of this short text leads to all the patriarchal narratives, especially Abraham cycle as part of the written traditions of Israel identity founders. The gestures of the same characters, often not valued in a theological analysis, are the expression of the beauty of this text. The three mysterious figures visiting the elderly Patriarch leave the divine mark of fulfilment of promises and assurance of joy that the birth of Isaac symbolizes